The rising tide of criticality in social entrepreneurship and social innovation - Timothy Curtis; Michael Bull; Vicky Nowak (Novation, 2022)
In this article, we trace a rising tide of criticality to highlight three waves in a sea of social entrepreneurship/social innovation (SE/SI) research. Our aim is to draw attention to counter, alternative and critical perspectives in the field and how ‘dangerous’ their co-option by right wing narratives is. We review what we believe to be three waves in the development of a critical research agenda undertaken by a cohort of academics who, in their loyalty to the field, have sought to unpick the underlying assumptions in the practice of, and academic reflection on, social innovation. We set out the early instrumentalist critique, in which the success and social utility of SE/SI is questioned. We secondly highlight a post-structuralist shift, in which hidden and unheard voices and perspectives are welcomed and celebrated. The third wave, for us, constitutes a dangerous threat to the SE/SI project, threatening to undermine and co-opt the first two waves, as has happened in other related fields of intellectual endeavour. We position this paper to not only engage with scholars who challenge the normative assumptions behind social innovation research, but also to draw attention to the entry of right-wing politics in post-modernist critical theory. It is not that everything in this third wave is bad, but that everything becomes unexpectedly dangerous, especially if we uncritically adopt reflexivity, naturalization and performativity as politically and morally neutral positions. Contra to Foucault, in adopting a critical realist stance, we begin to propose that ‘the social’, posed as an inherently ‘good’ thing, is an ontological reality that is knowable, albeit given that our knowledge of what is ‘good’ is nonetheless limited and partial. In the first Skoll World Forum (2004) some activists put up posters in the toilets of Said Business School warning delegates, ‘beware social entrepreneurship: a wolf in sheep’s clothes!’ (Nicholls & Young, 2008, p. 272). We conclude our paper warning that SE/SI is not the only wolf to be concerned about!